A dry etching process for N-polar III-V semiconductor materials

By using fluorine-containing etching gas in the dry etching process of N-polar Group III-V semiconductor materials, the etching conditions are optimized, and the problem of impurities adsorption on the surface of the material is solved, achieving lower roughness and better High etch controllability.

CN114551234BActive Publication Date: 2025-02-11GUANGDONG INST OF SEMICON IND TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210098255.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-25
Publication Date
2025-02-11
Estimated Expiration
2042-01-25

AI Technical Summary

Technical Problem

N-polar Group III-V semiconductor materials are more active and more likely to adsorb impurities, resulting in a significant increase in the roughness of the etching surface, affecting subsequent processes and device preparation.

Method used

Using a dry etching process, using ICP etching technology, the working gas contains boron trichloride, chlorine, argon and fluorine-containing ions. By adjusting the volume flow ratio of the gas, the etching conditions are optimized and the etching conditions are reduced. Adsorption of impurities on the surface of the material.

Benefits of technology

It effectively reduces the surface roughness of the material to reach 0.5~1nm (5×5μm2), improving the controllability of the etching process and device performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114551234B_ABST
    Figure CN114551234B_ABST
Patent Text Reader

Abstract

The present invention discloses a dry etching process for an N-polar III-V semiconductor material, and relates to the technical field of semiconductor materials. The dry etching process of the present invention comprises: performing ICP etching on an N-polar III-V semiconductor material, wherein the working gas comprises boron trichloride, chlorine, argon and an etching gas containing fluorine ions. The present invention selects the type of working gas so that the surface of the etched semiconductor material is smoother and has fewer impurities.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of semiconductor materials, and in particular to a dry etching process for an N-polarity III-V semiconductor material. Background Art

[0002] III-V materials have been more widely used in light-emitting devices, high-speed devices, high-temperature devices, high-frequency devices, and high-power devices due to their high carrier mobility and large bandgap. Among them, N-polar HEMT has lower ohmic contact resistance, better two-dimensional electron gas (2DEG) threshold and stronger short channel effect suppression ability due to its opposite polarity to traditional metal-polar HEMT, showing better device performance. However, studies have shown that N-polar III-V semiconductor materials are more active and more likely to absorb impurities, resulting in a significant increase in the roughness of the etched surface, which will have a great impact on subsequent processes and device preparation. Summary of the invention

[0003] The object of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a dry etching process for N-polar III-V semiconductor materials. The surface of the semiconductor material etched by the process has fewer impurities and is smoother.

[0004] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a dry etching process, wherein the dry etching process is: ICP etching of III-V semiconductor materials, and the working gas comprises boron trichloride (BCl3), chlorine (Cl2), argon (Ar) and an etching gas containing fluorine ions.

[0005] The traditional ICP etching process is mainly a Cl-based etching system. - The etching efficiency is high because the chemical reaction of the groups is the main one; Boron trichloride can bombard the water and oxygen in the reaction chamber, helping to reduce the generation of surface oxides; Ar gas forms Ar+ in the high-energy plasma system, which physically bombards the etching byproducts and can improve the etching uniformity. However, the inventors have found experimentally that N-polar III-V semiconductor materials are prone to adsorb impurities. It is difficult to achieve a smooth etching surface by using the method of etching metal-polar III-V semiconductor materials to etch N-polar III-V semiconductor materials. Through a large number of experiments, the inventors have found that after adding an etching gas containing fluorine ions to the working gas, the adsorption of impurities on the material surface is alleviated, and the surface roughness is lower.

[0006] Preferably, the III-V semiconductor material is Al(Ga)N.

[0007] Preferably, when the III-V semiconductor material is Al x Ga 1-x N, and x≥0.4, one-step etching is adopted, the volume flow rate of boron trichloride in the working gas is 5-10sccm, the volume flow rate of chlorine is 20-30sccm, the volume flow rate of argon is 5-15sccm, and the ratio of the volume flow rate of the etching gas containing fluorine ions to the total volume flow rate of boron trichloride and chlorine is 1:(10-32).

[0008] There is a synergistic and antagonistic relationship between different working gases. If the proportion of chlorine is too high, more impurities will be generated, and if the proportion is too low, the etching efficiency will be low. After the etching gas containing fluorine ions is introduced, the impurities can be removed, but when the proportion is too high, the etching rate will be significantly reduced, and new etching products will be generated on the surface of the material. When the volume flow ratio of the four gases meets the above restrictions, the etching process is more controllable, the impurities adsorbed on the material surface are less, and the roughness is lower.

[0009] Preferably, when the III-V semiconductor material is Al x Ga 1-x N, and x<0.4, a two-step etching method is adopted, in which boron trichloride, chlorine and argon are used for etching in the first step, and a fluorine ion-containing etching gas or a mixture of fluorine ion-containing etching gas and argon is used for dry cleaning in the second step; in the first step, the volume flow rate of boron trichloride is 5-10sccm, the volume flow rate of chlorine is 20-30sccm, and the volume flow rate of argon is 5-15sccm; in the second step, when the working gas is an etching gas containing fluorine ions, its volume flow rate is 10-15sccm, and when the working gas is a mixture of fluorine ion-containing etching gas and argon, the volume flow rate of the fluorine ion-containing etching gas is 1-7sccm, and the volume flow rate of argon is 8-14sccm.

[0010] As mentioned above, different etching objects have different etching byproducts, and the difficulty of desorption is also different. For the etching surface with high Ga content, the desorption of its etching byproducts is more difficult (GaCl3>AlCl3), and the one-step etching method will still leave more particles on the etching surface. The present invention uses a two-step method to etch the etching surface with high Ga content, which can make the etching surface smoother.

[0011] Preferably, the etching gas containing fluorine ions comprises at least one of SF6, CHF3, and CF4. Further preferably, the etching gas containing fluorine ions is SF6. Compared with other etching gases containing fluorine ions, the bombardment effect of SF6 is stronger, and after the same process, the surface roughness of the etched surface is lower.

[0012] Preferably, the conditions of the dry etching process are: ICP power 400-600W, RF bias power 100-200W, and gas pressure in the chamber 5-10mtorr.

[0013] The main function of the ICP power source is to generate high-density plasma and control the ion flux. When the power increases, the density of ions and active groups increases, and the etching rate also increases; but when it is too high, the uniformity will decrease, and it will also bring more heat load to the substrate, requiring a better temperature control system. The main function of the RF bias power source is to control the ion bombardment energy, which has a great influence on the etching rate and step angle. When the bias power increases, the etching rate increases significantly, but it will also cause the selectivity to decrease. When the bias power is too high, a "trenching" groove will sometimes be formed at the bottom of the step. The gas pressure has a great influence on the mean free path of the ions. When the gas pressure is low, the mean free path of the ions is very long, the directionality is very good, the ion bombardment effect is also strong, and it is also conducive to the desorption of volatile etching products. When the gas pressure is high, because the density of active groups and ions increases, the etching rate and selectivity will increase significantly. For the four etching gases selected by the present invention, when the etching conditions meet the above-mentioned limitations, the etching rate and etching effect can be balanced.

[0014] Preferably, before ICP etching the etching object, the etching object is ultrasonically cleaned with acetone, isopropanol and deionized water respectively, blown dry with nitrogen, and then the etching object is placed in the etching chamber for etching; or the nitrogen-dried sample is heat-baked, and then the dried sample is spin-coated with photoresist, pre-baked, exposed, developed, and post-baked, and then placed in the etching chamber for etching.

[0015] Preferably, the conditions for the heat baking are: temperature 100-120° C., time 5-15 min. Heat baking before spin coating can increase the adhesion of the glue.

[0016] Compared with the prior art, the present invention has the following beneficial effects: by selecting the type of etching gas and etching conditions, the present invention can reduce the surface roughness (RMS) of the material to 0.5-1 nm (5×5 μm) while performing efficient etching. 2 ). BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 OM images of etching products after etching for 4 minutes using the methods described in Example 1, Comparative Example 1 and Comparative Example 2;

[0018] Figure 2 The etching rate diagram of etching N-polar Al(Ga)N by the methods described in Example 1, Comparative Example 1 and Comparative Example 2;

[0019] Figure 3The etching time and impurity particle density distribution diagram of etching N-polar Al(Ga)N by the methods described in Example 1, Comparative Example 1 and Comparative Example 2;

[0020] Figure 4 The AFM images of N-polar Al(Ga)N before etching and after etching for 4 minutes in Example 1, Comparative Example 1 and Comparative Example 2;

[0021] Figure 5 The OM image (1) of the etched product after etching for 4 minutes using the method described in Example 2 and the OM image (2) of the photolithography product of step (2) of Example 2 after etching for 4 minutes using the method described in Comparative Example 1;

[0022] Figure 6 The AFM image (1) of the etched product after etching for 4 minutes using the method described in Example 2 and the AFM image (2) of the photolithography product of step (2) of Example 2 after etching for 4 minutes using the method described in Comparative Example 1. DETAILED DESCRIPTION

[0023] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0024] The etching equipment selected in the embodiments and comparative examples of the present invention is Oxford PlasmaLab System 133.

[0025] Example 1

[0026] An embodiment of the dry etching process of the present invention includes the following steps:

[0027] (1) The etching object is N-polar Al(Ga)N thin film material, which is divided into four layers from top to bottom, namely AlN, Al 0.4 Ga 0.6 N、Al 0.2 Ga 0.8 N, GaN, each layer has a thickness of 300nm; the etched objects are ultrasonically cleaned with acetone, isopropanol and deionized water respectively, and dried with nitrogen;

[0028] (2) Place the etched object in the reaction chamber of the ICP etcher, and introduce 8 sccm of BCl3, 24 sccm of Cl2, 5 sccm of Ar, and 3 sccm of SF6. The gas pressure in the chamber is 8 mtorr, the sample temperature is 20°C, the ICP power is 500 W, and the RF bias power is 150 W.

[0029] Example 2

[0030] An embodiment of the dry etching process of the present invention includes the following steps:

[0031] (1) The sample is an N-polar Al(Ga)N thin film material, which is divided into four layers from top to bottom: AlN, Al 0.4 Ga 0.6 N、Al 0.2 Ga 0.8 N, GaN, each layer has a thickness of 300nm; the etched objects are ultrasonically cleaned with acetone, isopropanol and deionized water, respectively, blown dry with nitrogen, and then baked on a hot plate at 110℃ for 10min;

[0032] (2) Using AZ 4620 photoresist, the above sample was spin-coated, pre-baked, exposed, developed, and post-baked to obtain an etching preparation sheet; the spin coating rate was 8000 rps, the time was 30 s; the pre-baking temperature was 105° C., the time was 90 s; the exposure time was 8 s; the development time was 3 min; the post-baking temperature was 105° C., the time was 3 min;

[0033] (3) Place the etched object in the ICP etcher reaction chamber, introduce 8 sccm of BCl3, 24 sccm of Cl2, 5 sccm of Ar, and 3 sccm of SF6, the pressure in the chamber is 8 mtorr, the sample temperature is 20 °C, the ICP power is 500 W, and the RF bias power is 150 W;

[0034] (4) After etching, use acetone, isopropyl alcohol and deionized water to ultrasonically clean and remove the glue.

[0035] Example 3

[0036] An embodiment of the dry etching process of the present invention includes the following steps:

[0037] (1) The etching object is N-polar Al(Ga)N thin film material, which is divided into four layers from top to bottom, namely AlN, Al 0.4 Ga 0.6 N、Al 0.2 Ga 0.8 N, GaN, each layer has a thickness of 300nm; the etched objects are ultrasonically cleaned with acetone, isopropanol and deionized water respectively, and dried with nitrogen;

[0038] (2) Place the etched object in the reaction chamber of the ICP etcher, introduce 5 sccm of BCl3, 30 sccm of Cl2, 10 sccm of Ar, and 2 sccm of SF6, the gas pressure in the chamber is 8 mtorr, the sample temperature is 20°C, the ICP power is 500 W, and the RF bias power is 150 W.

[0039] Example 4

[0040] An embodiment of the dry etching process of the present invention includes the following steps:

[0041] (1) The etching object is N-polar Al(Ga)N thin film material, which is divided into four layers from top to bottom, namely AlN, Al 0.4 Ga 0.6 N、Al 0.2 Ga 0.8 N, GaN, each layer has a thickness of 300nm; the etched objects are ultrasonically cleaned with acetone, isopropanol and deionized water respectively, and dried with nitrogen;

[0042] (2) Place the etched object in the reaction chamber of the ICP etcher, and introduce 8 sccm of BCl3, 24 sccm of Cl2, 15 sccm of Ar, and 1 sccm of SF6. The gas pressure in the chamber is 8 mtorr, the sample temperature is 20°C, the ICP power is 500 W, and the RF bias power is 150 W.

[0043] Example 5

[0044] An embodiment of the dry etching process of the present invention includes the following steps:

[0045] (1) The etching object is N-polar Al(Ga)N thin film material, which is divided into four layers from top to bottom, namely AlN, Al 0.4 Ga 0.6 N、Al 0.2 Ga 0.8 N, GaN, each layer has a thickness of 300nm; the etched objects are ultrasonically cleaned with acetone, isopropanol and deionized water respectively, and dried with nitrogen;

[0046] (2) Place the etched object in the reaction chamber of the ICP etcher, and introduce 8 sccm of BCl3, 24 sccm of Cl2, 5 sccm of Ar, and 5 sccm of SF6. The gas pressure in the chamber is 8 mtorr, the sample temperature is 20°C, the ICP power is 500 W, and the RF bias power is 150 W.

[0047] Example 6

[0048] An embodiment of the dry etching process described in the present invention. The difference between the dry etching process described in this embodiment and embodiment 1 is that in step (2), the volume flow rates of the gases are different, the volume flow rate of BCl3 is 10 sccm, the volume flow rate of Cl2 is 20 sccm, the volume flow rate of Ar is 15 sccm, and the volume flow rate of SF6 is 1 sccm.

[0049] Example 7

[0050] An embodiment of the dry etching process of the present invention includes the following steps:

[0051] (1) The etching object is N-polar Al(Ga)N thin film material, which is divided into four layers from top to bottom, namely AlN, Al 0.4 Ga 0.6 N、Al 0.2 Ga 0.8 N, GaN, each layer has a thickness of 300nm; the etched objects are ultrasonically cleaned with acetone, isopropanol and deionized water respectively, and dried with nitrogen;

[0052] (2) Place the etched object in the ICP etcher reaction chamber, introduce 8 sccm of BCl3, 24 sccm of Cl2, and 5 sccm of Ar, the pressure in the chamber is 8 mtorr, the sample temperature is 20°C, the ICP power is 500 W, the RF bias power is 150 W, and the etching time is 7 min;

[0053] (3) After step (2) is completed, stop introducing BCl3, Cl2 and Ar, and introduce SF6. The volume flow rate of SF6 is 15 sccm, the gas pressure in the chamber is 8 mtorr, the sample temperature is 20°C, the ICP power is 500 W, the RF bias power is 150 W, and the etching time is 3 min.

[0054] Example 8

[0055] An embodiment of the dry etching process of the present invention. The dry etching process of this embodiment is different from that of Embodiment 7 only in that SF6 and Ar are used simultaneously for etching in step (3), the volume flow rate of SF6 is 5 sccm, and the volume flow rate of Ar is 10 sccm.

[0056] Comparative Example 1

[0057] A dry etching process, the dry etching process comprising the following steps:

[0058] (1) The etching objects are N-polar Al(Ga)N thin film materials and Al-polar Al(Ga)N thin film materials. The N-polar Al(Ga)N thin film materials are divided into four layers from top to bottom, namely AlN, Al 0.4 Ga 0.6 N、Al 0.2 Ga 0.8 N, GaN, each layer has a thickness of 300nm; the etched objects are ultrasonically cleaned with acetone, isopropanol and deionized water respectively, and dried with nitrogen;

[0059] (2) The etched object is placed in the reaction chamber of the ICP etcher, and 8 sccm of BCl3, 24 sccm of Cl2 and 5 sccm of Ar are introduced. The gas pressure in the chamber is 8 mtorr, the sample temperature is 20°C, the ICP power is 500 W, and the RF bias power is 150 W.

[0060] Comparative Example 2

[0061] A dry etching process, the dry etching process comprising the following steps:

[0062] (1) The etching object is N-polar Al(Ga)N thin film material, which is divided into four layers from top to bottom, namely AlN, Al 0.4 Ga 0.6 N、Al 0.2 Ga 0.8 N, GaN; the etched objects were ultrasonically cleaned with acetone, isopropanol and deionized water respectively, and dried with nitrogen;

[0063] (2) Place the etched object in the reaction chamber of the ICP etcher, introduce 8 sccm of BCl3, 24 sccm of Cl2, 5 sccm of Ar, and 3 sccm of O2, the gas pressure in the chamber is 8 mtorr, the sample temperature is 20°C, the ICP power is 500 W, and the RF bias power is 150 W.

[0064] Performance Testing

[0065] The etching rate and surface roughness (RMS) of Examples 1 to 8 and Comparative Examples 1 to 2 were tested. The etching rate of Examples 1 to 6 was an average etching rate of 4 minutes of etching, and the etching rate of Examples 7 to 8 was an average etching rate of 7 minutes of etching in the first step and 3 minutes of dry cleaning in the second step; the surface roughness was tested using a Buraker atomic force microscope AFM (DimensionEdge); the test results are shown in Table 1.

[0066] Table 1

[0067]

[0068] It can be seen from the above test results that for the smooth surface samples, the surface roughness RMS of the samples etched by the method of the present invention is less than 1nm, and the etching effect is significantly better than that of the comparative example. In addition, from the test results of Examples 1 to 8, it can be seen that the etching rate of Example 5 is much lower than that of other examples. For industrial production, if the etching rate is lower than 80nm / min, the production efficiency will be greatly reduced and the economic benefits will be low. Therefore, controlling the ratio of the volume flow rate of the etching gas containing fluorine ions to the total volume flow rate of boron trichloride and chlorine gas to 1: (10 to 32) can ensure both a high etching rate and a good etching effect.

[0069] Figure 1 The OM images of the etched products after etching for 4 minutes by the methods described in Example 1, Comparative Example 1 and Comparative Example 2 show that the surfaces of the etched products of Example 1, Comparative Example 1 (Al polarity) and Comparative Example 2 are smooth and particle-free, indicating that the BCl3, Cl2, Ar, SF6 system and the BCl3, Cl2, Ar, O2 system can inhibit the adsorption of impurities on the surface of the material; after etching Al polarity Al(Ga)N by the method described in Comparative Example 1, no impurities appear on the surface of the material, but after etching N polarity Al(Ga)N by the method described in Comparative Example 1, a large amount of Al(Ga)Cl x Etching byproducts (the insets are SEM and EDS images). The results show that even if the etching conditions are the same, the results produced are completely different when the etching objects are different.

[0070] Figure 2 The etching rate diagram of N-polar Al(Ga)N is shown in Example 1 (SF6 is introduced), Comparative Example 1 (no O2 or SF6), and Comparative Example 2 (O2 is introduced). Figure 2 It can be seen that the three etching methods all have high etching rates, among which the etching rate of Example 1 is about 100 nm / min, and the controllability is stronger. Figure 3 The following is a graph showing the distribution of the etching time and impurity particle density of N-polar Al(Ga)N using the methods described in Example 1, Comparative Example 1, and Comparative Example 2. As can be seen from the graph, compared with Comparative Example 1, there is almost no particle on the surface of the etched product of Comparative Example 2 and Example 1 after etching for 5 minutes. As the etching depth increases, when etching to Al 0.2 Ga 0.8 When the N layer is formed (etching for 5 to 6 minutes), a small amount of impurity particles appear on the surface of the sample, but the particle density is still very low, much less than that of Comparative Example 1.

[0071] Figure 4 The AFM images of the samples before N-polar Al(Ga)N etching and after etching for 4 minutes using the methods described in Example 1, Comparative Example 1, and Comparative Example 2. As can be seen from the figure, after etching using the method described in Comparative Example 1, the 5×5 μm 2 The surface roughness is about 1.1nm. After O2 is introduced, although the etching byproduct Al(Ga)Cl x The generation of impurities is suppressed, but due to the oxidation of O2 on the etched surface, an island structure is formed with a surface roughness (RMS) of 7.6nm (5×5μm 2 ), which is higher than before etching. After SF6 is introduced, the etching byproduct Al(Ga)Cl xThe generation of impurities is also suppressed, and the surface roughness (RMS) of the material can reach 0.56nm (5×5μm 2 ), which is smaller than the 0.67nm (5×5μm 2 In addition, it can be seen from the AFM image that the N-polar Al(Ga)N etched with SF6 has the best surface uniformity.

[0072] Figure 5 The OM image (1) of the etched product after etching for 4 minutes using the method described in Example 2 and the OM image (2) of the photolithography product of step (2) of Example 2 after etching for 4 minutes using the method described in Comparative Example 1; Figure 6 The AFM image (1) of the etched product after etching for 4 minutes using the method described in Example 2 and the AFM image (2) of the photolithography product after etching for 4 minutes using the method described in Comparative Example 1. Figure 5 (1) and Figure 5 The test results of (2) show that after etching by the method described in Example 2, there are almost no impurities on the surface of the etched product, while after etching by the method described in Comparative Example 1, the surface of the etched product contains more impurities; Figure 6 (1) and Figure 6 The test results of (2) also show that after etching by the method described in Example 2, the surface roughness is significantly lower than the surface roughness of the etched product after etching the photolithography product by the method described in Comparative Example 1. The above results show that the method of the present invention is also suitable for etching photolithography products.

[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A dry etching process for N-polar III-V semiconductor materials, characterized in that: The dry etching process is: ICP etching of III-V semiconductor materials, the working gas comprising boron trichloride, chlorine, argon and etching gas containing fluorine ions; The III-V semiconductor material is Al x Ga 1-x N; When x≥0.4, one-step etching is adopted, the volume flow rate of boron trichloride in the working gas is 5-10sccm, the volume flow rate of chlorine is 20-30sccm, the volume flow rate of argon is 5-15sccm, and the ratio of the volume flow rate of the etching gas containing fluorine ions to the total volume flow rate of boron trichloride and chlorine is 1:(10-32); When x is less than 0.4, a two-step etching method is adopted. In the first step, boron trichloride, chlorine and argon are used for etching. In the second step, an etching gas containing fluorine ions or a mixture of etching gas containing fluorine ions and argon is used for dry cleaning. In the first step, the volume flow rate of boron trichloride is 5 to 10 sccm, the volume flow rate of chlorine is 20 to 30 sccm, and the volume flow rate of argon is 5 to 15 sccm. In the second step, when the working gas is an etching gas containing fluorine ions, its volume flow rate is 10 to 15 sccm. When the working gas is a mixture of etching gas containing fluorine ions and argon, the volume flow rate of the etching gas containing fluorine ions is 1 to 7 sccm, and the volume flow rate of argon is 8 to 14 sccm.

2. The dry etching process according to claim 1, characterized in that: The fluorine ion-containing etching gas includes at least one of SF6, CHF3, and CF4.

3. The dry etching process according to claim 1, characterized in that: The etching gas containing fluorine ions is SF6.

4. The dry etching process according to claim 1, characterized in that: The etching conditions of the dry etching process are: ICP power 400-600W, RF bias power 100-200W, and gas pressure in the chamber 5-10mtorr.

5. The dry etching process according to claim 1, characterized in that: First, the etching object is ultrasonically cleaned with acetone, isopropanol and deionized water respectively, blown dry with nitrogen, and then the etching object is placed in the etching chamber for etching; or the dried sample is spin-coated with photoresist, pre-baked, exposed, developed, and post-baked, and then placed in the etching chamber for etching.

Citation Information

Patent Citations

  • GaN-based vertical structure light-emitting diode and preparation method thereof

    CN101789473A

  • SELECTIVE DRY ETCHING OF N-FACE (Al,In,Ga)N HETEROSTRUCTURES

    US20130099277A1